Editorial. (1st January 2012) - Sifaleras, Angelo; Papathanasiou, Jason; Demange, Marc
This editorial describes the special issue on 'New combinatorial optimisation models for decision-making' of the International Journal of Applied Management Science (IJAMS) . It provides a short review of combinatorial optimisation applications in decision-making, specifies the aim of the special issue, and finally presents an overview of five papers in the issue.